Alfred Adler papers - Adler, Alfred, 1870-1937.
Correspondence, memoranda, lectures, writings, reports, notes, patient case studies and record books, appointment book, certificates, clippings, printed matter, photographs, and other papers relating to Adler's career as a psychologist. Includes a letter (1937) written by Albert Einstein comparing theories of Adler and Sigmund Freud. Other correspondents include Adler's wife, Raissa Epstein Adler, and their children and G. Margery Allen.
Microfilm edition available for a portion of the collection
Microfilm produced from originals in the Manuscript Division.
Library of Congress Rare Book and Special Collections Division.
Psychologist.
Collection material in German and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adler, Raissa Epstein -- Correspondence; Allen, G. Margery -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Adler family; Psychology; Psychologists